2009
DOI: 10.1007/s10548-009-0104-7
|View full text |Cite
|
Sign up to set email alerts
|

Similarities Between Simulated Spatial Spectra of Scalp EEG, MEG and Structural MRI

Abstract: Electrical dipoles oriented perpendicular to the cortical surface are the primary source of the scalp EEGs and MEGs. Thus, in particular, gyri and sulci structures on the cortical surface have a definite possibility to influence the EEGs and MEGs. This was examined by comparing the spatial power spectral density (PSD) of the upper portion of the human cortex in MRI slices to that of simulated scalp EEGs and MEGs. The electrical activity was modeled with 2,650 dipolar sources oriented normal to the local cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Because the spatial texture of EEG is spatially mostly noncyclic, it would be more robust to have the sample frequency 3-5 times higher than the frequency limit (Barlow, 1993), which would yield interelectrode spacing of about 3-5 mm in neonates and 5-8 mm in adults. Simulations with adult head model have even suggested need for interelectrode spacing as low as 3 mm (see Ramon et al, 2009). The inflection point on the left side (0.5 cycles/cm in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because the spatial texture of EEG is spatially mostly noncyclic, it would be more robust to have the sample frequency 3-5 times higher than the frequency limit (Barlow, 1993), which would yield interelectrode spacing of about 3-5 mm in neonates and 5-8 mm in adults. Simulations with adult head model have even suggested need for interelectrode spacing as low as 3 mm (see Ramon et al, 2009). The inflection point on the left side (0.5 cycles/cm in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A good question to ask is how many electrodes are needed to properly sample the spatial information embedded in EEG or ECoG data which are generated from the electrical activity of the distributed cortical sources in the gray matter. A simulation study has shown that to pick up the gyral structures related effects in the scalp EEG, possibly, a 3.0 mm interelectrode separation will be necessary [21]. This simulation study was performed with a finite element method (FEM) model of an adult male with 2 mm  2 mm  3.2 mm size voxels.…”
Section: Spatial Power Spectral Densitiesmentioning
confidence: 99%
“…The x coordinate is in the sagittal plane, increasing from anterior (front) to the posterior (back) of the subject. The spatial PSD in the x direction is named as PSDx [21]. However, often, many authors use the symbol PSDx for any spatial direction, whether it is x, y or z [11,22].…”
Section: Spatial Power Spectral Densitiesmentioning
confidence: 99%
See 2 more Smart Citations